Curved layer based process planning for multi-axis volume printing of freeform parts. (September 2019) - Xu, Ke; Li, Yingguang; Chen, Lufeng; Tang, Kai
Abstract: The traditional 2.5-axis volume printing process purely relies on planar and parallel slicing layers, which imperatively requires the support structure when dealing with overhanging features on the part. The advent of multi-axis additive manufacturing inaugurates a brand new type of printing process with an adjustable build direction, based on which the support structure can be successfully reduced (if not completely eliminated) upon a proper process planning. Presented in this paper is a curved layer based process planning algorithm for multi-axis printing of an arbitrary freeform solid part. Given a freeform solid model represented as a watertight mesh surface, our algorithm starts with the establishment of a surface embedded field, whose value at any particular point is exactly the geodesic distance to the specified bottom of the model. Any iso-level contour induced from this field is first flattened, filled by a Delaunay triangular mesh, and then mapped back to 3D space through the Harmonic mapping to interpolate the original 3D contour, thus generating a curved layer. After the entire model is decomposed into curved layers by the proposed adaptive slicing strategy, the multi-axis printing paths are then generated on these layers in a contour-parallel fashion. Finally, following the strict increasing order of iso-levels, the contours are printed one by one till the final formation of the part. Preliminary tests in both computer simulation and physical printing of our algorithm have given a positive validation on its effectiveness and feasibility in eliminating the need of support structure. Highlights: A general multi-axis volume printing process planning is devised for freeform parts. The part surface is associated with an embedded geodesic distance field. The iso-level contours extracted from the embedded field are constructed in curved layers following a dedicated algorithm. The adaptive slicing strategy together with the multi-axis printing path generation helps to fabricate the freeform solid in a support-free manner.